A tale of two diseases: Sarcoidosis, COVID-19 and new therapeutic options with dual RAS inhibition and tetanus-diphtheria vaccine. (July 2021) - Ozbalci, Demircan
Abstract: Sars Cov-2, the pathogen which belongs to the beta coronavirus family that is responsible for COVID-19, uses Angiotensin Converting Enzyme 2 (ACE2) as a receptor, which is responsible for controlling the actions of renin-angiotensin system (RAS). Sars Cov-2 - ACE2 binding leads to a RAS mediated immune response, which targets especially lungs to form ARDS, which in turn, is the most important cause of mortality in COVID-19. CD8 + T cell response dominates over CD4 + T cell response and natural killer cell dysfunction also leads to CD4 + cell dysfunction in COVID-19; this immune dysregulation leads to inappropriate (ARDS) and inadequate (low or quickly waning antibodies) responses to the disease and unfortunately, prepares the patients for re-infections. The peripheral anergy seen in chronic sarcoidosis has much resemblance to COVID-19; CD8 + T cell accumulation is also responsible for inadequate reaction to tuberculin and antigenic stimulus. This article, based on the similarity of COVID-19 and sarcoidosis, discusses a combination of the therapeutic strategy of the tetanus-diphtheria vaccine and dual RAS inhibition, alongside with hydroxychloroquine and antiviral agents, as a solution to overcome the problems described above.